Balto-Slavic personal pronouns and their accentuation - Kortlandt, Frederik (Baltistica, 2013)
The major difference between Kapović’s reconstructions and mine is the huge number of doublets which he assumes for his proto-languages. It is reasonable to assume that much of this variation is secondary and must not be dated back to the proto-language.The acute of 1st pl. *noʔs and 2nd pl. *woʔs is not the result of “monosyllabic lengthening” but originated from the initial zero grade of PIE acc. *nsme and *usme. Kapović’s hypothesis of a PIE subphonemic lengthening yielding an acute in monosyllabic pronominal forms must be rejected.Pronominal paradigms were stressed on the initial syllable in Balto-Slavic. However, prepositional groups were also stressed on the initial syllable, e.g. Prussian ēnmien ‘in me’, prēimans ‘to us’, pērwans ‘for you’, also Russian tudá, ottúda ‘from there’, nel’zjá, donél’zja ‘as can be’, Ukr. mené, do méne ‘to me’, SCr. vráta, nà vrāta ‘on the door’, all of which became stressed on the second syllable as a result of Dybo’s law. Traces of this distribution can be found in Serbo-Croatian, Slovene, Old Russian, Middle Bulgarian and Polabian.Since the Slavic pronouns belong to accent patterns (a) and (b), not (c), they never have an original falling tone. Kapović mistakenly assumes an original circumflex in Proto-Slavic *ty, *my, *vy.
Keywords: Balto-Slavic; accentology; accentuation; personal pronouns; historical morphology